2019
DOI: 10.1161/strokeaha.118.023445
|View full text |Cite
|
Sign up to set email alerts
|

Lesion Localization of Poststroke Lateropulsion

Abstract: Background and Purpose: Hemispheric stroke studies associating lateropulsion (pusher syndrome) with the location of brain lesions have had mixed results from small, unmatched samples. This study was designed to determine whether lateropulsion localizes to specific brain regions across patients with stroke using a case-control design. Methods: Fifty patients with lateropulsion following stroke were matched with 50 stroke patients without lateropulsion using age, time since onset of stroke, admission motor Funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 33 publications
(55 reference statements)
3
39
0
3
Order By: Relevance
“…Previous studies suggested that disruption of networks in the right hemisphere could impair vertical postural control and lead to lateropulsion [ 5 ]. The postcentral gyrus and surrounding white matter, and the postcentral gyrus and Brodmann area 40 in the inferior parietal lobe, were reportedly associated with lateropulsion [ 3 , 7 , 27 ]. Damage to the inferior frontal gyrus and precentral gyrus was previously reported to be associated with lateropulsion [ 3 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies suggested that disruption of networks in the right hemisphere could impair vertical postural control and lead to lateropulsion [ 5 ]. The postcentral gyrus and surrounding white matter, and the postcentral gyrus and Brodmann area 40 in the inferior parietal lobe, were reportedly associated with lateropulsion [ 3 , 7 , 27 ]. Damage to the inferior frontal gyrus and precentral gyrus was previously reported to be associated with lateropulsion [ 3 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The postcentral gyrus and surrounding white matter, and the postcentral gyrus and Brodmann area 40 in the inferior parietal lobe, were reportedly associated with lateropulsion [ 3 , 7 , 27 ]. Damage to the inferior frontal gyrus and precentral gyrus was previously reported to be associated with lateropulsion [ 3 , 27 , 28 ]. The insula may play a role in vestibular function [ 29 ], and damage in this area might disrupt the vestibulospinal system and induce lateropulsion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The structural biology of verticality perception is incompletely understood; however, studies of voxel-based lesion-behavior mapping and neuronal network-based mathematical modeling (57), have shown a clear involvement of posterior nuclei of the thalamus. What remains unclear is whether degeneration of the thalamic nuclei is a common feature when primary lesions are outside thalamus, and whether symptom-lesion association is confined to specific posterior nuclei of the thalamus.…”
Section: Introductionmentioning
confidence: 99%